The Influence of Perceived Usefulness, Satisfaction, and Personalization on Subscription Video on Demand Continuance Intentions - Natasya Elora Carissa; Muhammad Erlangga; Cindy Sonesha Evik; Putu Wuri Handayani (CommIT (Communication and Information Technology) Journal, 2023)
The rapid development of Subscription Video on Demand (SVoD) services in Indonesia makes it promising. The change in consumers’ behavior from watching movies through television channels and cinemas to online streaming has encouraged industry players to look for innovation. The research aims to analyze factors influencing the intention to continue using SVoD with Netflix as the case study. The research combines two theories, namely Information System Success (ISS) Model and Expectation Confirmation Theory (ECT). The research also adds an aspect of personalization which is one of the characteristics of SVoD services. There are 623 respondents who have used Netflix’s SVoD service at least once (purposive sampling) to participate in the research. The data are analyzed using the covariancebased structural equation model and facilitated using AMOS 26 program. The results indicate that service quality has a positive effect on confirmation. Then, system quality has a positive effect on perceived usefulness, and confirmation has a positive effect on satisfaction. Moreover, satisfaction, perceived usefulness, and personalization positively affect continuance intention to use SVoD services. Based on these results, the research is expected to contribute to SVoD service providers to evaluate their services so that users have the intention to continue using the SVoD services.